2021
DOI: 10.7150/thno.48206
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of long extracellular RNAs reveals a detection panel of noncoding RNAs for liver cancer

Abstract: Rationale: Long extracellular RNAs (exRNAs) in plasma can be profiled by new sequencing technologies, even with low abundance. However, cancer-related exRNAs and their variations remain understudied. Methods: We investigated different variations (i.e. differential expression, alternative splicing, alternative polyadenylation, and differential editing) in diverse long exRNA species (e.g. long noncoding RNAs and circular RNAs) using 79 plasma exosomal RNA-seq (exoRNA-seq) datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 68 publications
0
48
0
Order By: Relevance
“…In addition to 35 datasets for liver cancer and 30 datasets for healthy donors we published previously (GSE142987) 21 , 230 raw FASTQ les supporting the ndings of this study are available in the Gene Expression Omnibus (GEO: GSE174302).…”
Section: Data Availabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to 35 datasets for liver cancer and 30 datasets for healthy donors we published previously (GSE142987) 21 , 230 raw FASTQ les supporting the ndings of this study are available in the Gene Expression Omnibus (GEO: GSE174302).…”
Section: Data Availabilitymentioning
confidence: 98%
“…The cohort in this study included 295 plasma samples in total. Except for 65 previously published samples (GSE142987: 35 liver cancer patients and 30 healthy donors) [21] , we sequenced the total cfRNAs (>50nt) in 230 additional plasma samples (54 colorectal cancer, 37 stomach cancer, 27 liver cancer, 35 lung cancer, 31 esophageal cancer and 46 HDs).…”
Section: Cohort Design and Sample Collectionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are non-coding transcripts of 200 nucleotides in length, which could regulate the expression of various cancer-associated genes. Recently, Zhu et al comprehensively investigated the molecular profiles of lncRNAs in plasma samples from HCC patients and revealed that the differentially expressed lncRNAs were mainly enriched in the biological functions related to tumorigenesis, such as cell metastasis, immune response, and metabolism regulation (11). A high level of LINC00958 aggravated HCC lipogenesis and progression through sponging miR-3619-5p, further upregulating the hepatoma-derived growth factor expression (12).…”
Section: Introductionmentioning
confidence: 99%
“…As single markers sometimes lack sensitivity and specificity, designing biomarker panels has been suggested as a good option for early detection, diagnosis, and prediction of recurrence. Such panels of lncRNAs have already been proposed for hepatocellular [253], liver [254], bladder [255,256], breast and cervical cancer [257]. A lncRNA panel as a candidate prognostic biomarker for OC has been proposed by Zhan et al [258], but the focus was mainly on the construction of panels that can assess the response to therapy of OC patients, for example for platinum-based chemoresistance [259,260] or paclitaxel resistance [261].…”
Section: Circulating Lncrnas As Diagnostic and Prognostic Biomarkers For Ocsmentioning
confidence: 99%